Research on the Design and Development of Shenyang Qing Culture derivatives under the Background of Cultural and Tourism Integration - Zhu, Heng (Transactions on Social Science, Education and Humanities Research, 2024)
The current international situation is unprecedented and reflected in various industries, especially the recovery of the international tourism industry is still a very difficult process, in the face of the international environment, domestic tourism is not all a crisis, but crisis and opportunity coexist. Shenyang, as an ancient capital of one dynasty, integrates Manchu culture into cultural and creative derivative products and integrates it with modern design applications, and creates the urban cultural brand of "Shengjing", which is conducive to improving the popularization scope and publicity effect of Manchu culture, and improving the participation and interaction of Manchu cultural tourism. And can drive the development of qing cultural derivatives design industry.